Star-spot distributions and chromospheric activity on the RS CVn type eclipsing binary SV Cam. Issue 1 (6th June 2018) - Şenavcı, H V; Bahar, E; Montes, D; Zola, S; Hussain, G A J; Frasca, A; Işık, E; Yörükoğlu, O
ABSTRACT: Using a time series of high-resolution spectra and high-quality multicolour photometry, we reconstruct surface maps of the primary component of the RS CVn type rapidly rotating eclipsing binary, SV Cam (F9V + K4V). We measure a mass ratio, q, of 0.641(2) using our highest quality spectra and obtain surface brightness maps of the primary component, which exhibit predominantly high-latitude spots located between 60° and 70° latitudes with a mean filling factor of ∼35 per cent. This is also indicated by the R -band light-curve inversion, subjected to rigorous numerical tests. The spectral subtraction of the H α line reveals strong activity of the secondary component. The excess H α absorption detected near the secondary minimum hints to the presence of cool material partially obscuring the primary star. The flux ratios of Caii IRT excess emission indicate that the contribution of chromospheric plage regions associated with star-spots is dominant, even during the passage of the filament-like absorption feature.